CODE SWITCHING USED BY BILINGUAL TEACHERS AT RSBI (RINTISAN SEKOLAH BERBASIS INTERNASIONAL) IN MAKASSAR - Rabiatul Adawiah (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2019)
English is a need in this era. Most education activities are conducted using and integrating with this global language. The objectives of this research are 1) types of code switching are mostly used by a bilingual teacher; 2) the bilingual teacher’ reasons in use of code switching in class. SMPN 12 Makasar applied bilingual class in Math, Science and English subjects. And this research focussed on a Math teacher as the research subject. Qualitative method was used by combining observation and interview. This research shows that math teacher used code switching in opening, main and closing session. There are three types of code switching used by math teacher. They are inter-sentential, intra-sentential dan tag switching. Bilingual teacher combined Bahasa dan English because of some reasons; talking about a particular topic, inserting sentence fillers of connectors, using repetition used for clarification, softing request and command, being aare of real lexical need, and intention of clarifying the speech content for interlocutor. Key words: Code Switching, Bilingual, Math Teacher